STUDY ON THE SUSPENDED SOLIDS IN THE WEST COASTAL WATERS OF BENGKALIS - Arif Teguh Satria; Rifardi '; Elizal ' (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2014)
This study was carried out in May 2012. It aimed to find out on the stageextent of suspended solid in the west coastal waters of Bengkalis, in Riauprovince. This study used survey method and van Dorn sampler to collect thewater samples at 7 stations of the study area. The National Standard Method ofIndonesia for suspended solid analysis was used to deal with the main goal of thestudy. The result showed that the average stage of suspended solid was differentfor all stations. The considerable one was found in the station 4 comparing to theother stations. It caused station 4 was located at the confluence of the tidal currentpatterns come from the Malacca Strait low tide that come with the current of theriver around the west coastal water of Bengkalis.Key word : Suspended Solids, Water Of Bengkalis